2022
DOI: 10.1029/2022gl099727
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Role of Convection in Future Hourly Rainfall Extremes Over South Korea

Abstract: An increasing number of studies have examined the dependence of sub-daily extreme rainfall intensity on the surface air temperature, so-called extreme precipitation-temperature (EP-T) scaling as reviewed by Fowler et al. ( 2021). The scaling rates identified in the observations were found to be larger than the theoretical limit of the Clausius-Clapeyron (C-C) relation, suggesting disproportionate intensification of sub-daily precipitation extremes in a warmer condition. Several observational studies confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…However, even the largest temperature increases cannot mitigate the impact of greater precipitation on increasing flood magnitude and frequency. Furthermore, this uncoupled model does not include realistic changes in rainfall intensity and magnitude which might be expected with increases in temperature and could change land surface responses to floods and droughts (Wasko et al, 2019;Lee et al, 2022).…”
mentioning
confidence: 99%
“…However, even the largest temperature increases cannot mitigate the impact of greater precipitation on increasing flood magnitude and frequency. Furthermore, this uncoupled model does not include realistic changes in rainfall intensity and magnitude which might be expected with increases in temperature and could change land surface responses to floods and droughts (Wasko et al, 2019;Lee et al, 2022).…”
mentioning
confidence: 99%
“…compared to the ERA-Interim (Hersbach et al 2020). All these reference datasets have been widely used in climate model evaluation (Park et al 2021(Park et al , 2022Lee et al 2022;Tang et al 2022;T. J. Kim et al 2023;) and were interpolated to the same 0.25° × 0.25° grids using the bilinear interpolation method.…”
Section: Observation and Reanalysis Datasetsmentioning
confidence: 99%
“…An inaccurate MCS life cycle often leads to erroneous circulation (Marsham et al, 2013;Birch et al, 2015;Willetts et al, 2017), unrealistic cloud cover, and climate sensitivity (Zhao, 2014;Bony et al, 2015) in models. Recently, with the help of model simulations, it was found that the super Clausius-Clapeyron scaling of precipitation with the temperature was largely due to the better organization of MCSs (Bao et al, 2017;Lee et al, 2022). Thus, knowledge of various characteristics of deep clouds is needed to test and improve the present-day high-resolution weather models.…”
Section: Introductionmentioning
confidence: 99%